Оценка характеристик канала радиосвязи в морской среде; Журнал технической физики; Т. 92, № 9 - Лукин А. Ф. Александр Федорович; Томилин А. К. Александр Константинович; Гульков А. Н. Александр Нефедович; Кремс К. А. Константин Арнольдович (2022, 2022)
Заглавие с экрана